EMPOWERING BAWEAN ISLAND COASTAL COMMUNITIES THROUGH FISH CRACKERS PRODUCT BRANDING AND MARKETING - Gabriel, Azmi Alvian; Malik, Ahmad Dahlan; Halim, Abdul; Prihastiti, Adinda Siska; Kamaliyah, Nurul (Universitas Sahid, 2024)
Bawean Island is included in the extraterritorial area of Gresik Regency, which has large natural resources in both the fisheries and agricultural sectors. If properly managed, this circumstance has the potential to lead to regional economic development. Accelerating economic activity, particularly in Bawean Island's coastal regions, can be done by developing downstream products and creating an integrated marketing model. The objective of this community service project is to support the growth and marketing of SMEs processed fish products in Dayasungai Hamlet, Sungairujing Village, Sangkapura District, and Bawean Regency as a strategic step in boosting the regional economy of coastal communities. Dayasungai Hamlet is home to 45 families, 90% of which make fish crackers. The potential of fish cracker products to penetrate wider marketing areas has been hampered by their simple packaging and scant information. Training in GMP, business and financial management, product development and packaging, and digital marketing can enhance community knowledge and boost the desire to implement business management practices, achieving an average score of 90%. Product rebranding results in comprehensive information and a better product identity, which makes it more likely to be positively received by consumers showed by product sales increase average of 154.7% per month.